Leaves of isoprene‐emitting tobacco plants maintain PSII stability at high temperatures. Issue 3 (15th May 2019) - Pollastri, Susanna; Jorba, Ignasi; Hawkins, Timothy J.; Llusià, Joan; Michelozzi, Marco; Navajas, Daniel; Peñuelas, Josep; Hussey, Patrick J.; Knight, Marc R.; Loreto, Francesco
Summary: At high temperatures, isoprene‐emitting plants display a higher photosynthetic rate and a lower nonphotochemical quenching (NPQ) compared with nonemitting plants. The mechanism of this phenomenon, which may be very important under current climate warming, is still elusive. NPQ was dissected into its components, and chlorophyll fluorescence lifetime imaging microscopy (FLIM) was used to analyse the dynamics of excited chlorophyll relaxation in isoprene‐emitting and nonemitting plants. Thylakoid membrane stiffness was also measured using atomic force microscope (AFM) to identify a possible mode of action of isoprene in improving photochemical efficiency and photosynthetic stability. We show that, when compared with nonemitters, isoprene‐emitting tobacco plants exposed at high temperatures display a reduced increase of the NPQ energy‐dependent component ( qE ) and stable (1) chlorophyll fluorescence lifetime; (2) amplitude of the fluorescence decay components; and (3) thylakoid membrane stiffness. Our study shows for the first time that isoprene maintains PSII stability at high temperatures by preventing the modifications of the surrounding environment, namely providing a more steady and homogeneous distribution of the light‐absorbing centres and a stable thylakoid membrane stiffness. Isoprene photoprotects leaves with a mechanism alternative to NPQ, enabling plants to maintain a high photosynthetic rate at rising temperatures.